QUALITY CULTURE OF ISLAMIC BOARDING SCHOOL - Muhith, Abd. (International Journal of Research -GRANTHAALAYAH, 2018)
The existence and role of Islamic boarding schools in the field of social life of the community requires serious attention. Proper management and provision and improvement of human resources in the field of management. Inequality between large boarding schools and small Islamic boarding schools is clearly seen in the management of pesantren. Culture is an obstacle in conducting pesantren activities. The quality of pesantren is formulated based on management which is carried out in a tangible process starting from planning, organizing, implementing and monitoring carried out to determine or resolve predetermined goals using people and other resources. This type of research uses ethnography with qualitative research methods with descriptive analysis. The research findings focused on pesantren quality culture models that formulated the problem in more detail so that researchers used a qualitative approach with an in-depth interview observation. The conclusion of the results of this study is the quality of pesantren culture embodied in the form of organizational culture that is used as a system of values, beliefs, assumptions, or norms that have been applied, agreed upon and followed by members of the organization as a code of conduct for pesantren activities, madrasas and schools.